Coating Graphene Oxide On Bronze (G-CU SN10) By Using Electrochemical Deposition To Improve Its Corrosion Resistance - مسلم همام; علي هترة; عزت حسن (Latakia University Journal -Engineering Sciences Series, 2024)
This research aims to shed light on the role of graphene in resisting corrosion occurring in DIN1705 graded bronze, which is widely used in manufacturing pump impellers. A layer of graphene oxide prepared using Hummer’s method was deposited on the surface of the metal using electrochemical deposition technology, and The covering layer was confirmed using an X-ray diffraction device (XRD) and electron microscope (SEM). An immersion corrosion test was conducted on the metal in a medium containing a sodium hypochloride solution. The rate of corrosion resulting from the decrease in weight was calculated, and the results were compared to a non-corrosive sample. Covered, as the results indicated an increase in the corrosion resistance of the sample covered with graphene oxide at the expense of the other sample, which clarifies the importance of graphene oxide as a corrosion resistant.